Conjugated Cobalt Phthalocyanine as Durable Electrode Materials for Lithium-Ion Storage. Issue 10 (8th October 2021) - Xu, Shaofeng; Kong, Weiqiang; Cui, Liying; Wen, Zhongsheng
Abstract : Cobalt phthalocyanine material is successfully applied as active materials for lithium-ion batteries for the first time. Amazing activity of the as-prepared CoPPc with the capability of reversible Li-ion insertion/extraction is demonstrated experimentally with long cycle life and a relatively high capacity. It delivers a reversible discharge capacity of 514 mA h g −1 at 200 mA g −1 after 550 cycles. The successful application of cobalt phthalocyanine provides a new approach for the development of electrode materials for lithium-ion batteries.